82.6k views
2 votes
Simplify 3-9 (-2 + x) -9x

1 Answer

4 votes
You would use the distributive property and addition to simplify this equation.

Let's start from left to right:

3-9= -6

Distribute -6 through to -2 and positive x:

-6(-2)= 12 (negatives cancel each other out and become positive)

-6(x)= -6x

New equation;

12-6x-9x

Now we would add together like the terms (x):

-6x+(-9x)= -15x

Don't forget that 12!

12-15x is your simplified answer.

Hope that helps explains!
User Basil Musa
by
5.8k points